Numerical Analysis of Bearing Behavior of the Prebored Precast Pile with an Enlarged Base - Zao Ling; Jiangbin Wu; Weidong Wang (Advances in Civil Engineering)
Prebored precast pile with an enlarged base (PPEB pile) is a new type of green and environmental protection pile foundation developed in China in recent years, which has complex bearing characteristics and many influencing factors. Based on the static load tests and key parameters’ tests in deep soft soil in Shanghai, a three-dimensional numerical analysis model was established using ABAQUS finite element software. The transfer law of load among the precast pile, cement soil, and soil around the pile and the action mechanism of the enlarged base were analyzed emphatically, and a sensitivity analysis of the main factors affecting the bearing performance was carried out. The calculation results show that the existence of the enlarged base can greatly improve the compressive bearing capacity, increasing the diameter and height of the enlarged base is beneficial to the bearing capacity, and the influence of the diameter expansion ratio is more effective. With the increase of the proportion of nodular piles, the ultimate bearing capacity increases slightly, but the deformation increases obviously. Under the condition of cement soil of the test piles, the spacing of the neighboring nodules of nodular piles has no obvious effect on the bearing capacity, and the 1 m spacing commonly used in engineering applications can be optimized. The increase of cement soil thickness is beneficial to the improvement of pile bearing capacity, but the efficiency is low. Finally, some improvement measures for the construction technology of the PPEB pile were put forward.